2015
DOI: 10.1190/tle34020206.1
|View full text |Cite
|
Sign up to set email alerts
|

2D time-lapse seismic tomography using an active time-constraint (ATC) approach

Abstract: A 2D seismic time-lapse inversion approach can image the evolution of seismic velocities over time and space. The forward modeling is based on solving the eikonal equation using a second-order fast-marching method. Wave paths are represented by Fresnel volumes rather than by conventional rays. This approach accounts for complex velocity models and has the advantage of considering the effects of wave frequency on velocity resolution. The aim of time-lapse inversion is to find changes in velocities of each cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Day-Lewis et al (2002) and Johnson et al (2007) proposed a difference tomography scheme specifically devised to invert time-lapse crosswell amplitude data to map changes in electric conductivity consecutive to a saline tracer test. Very recently, Karaoulis et al (2015) used an active time-constraint approach to invert time-lapse traveltime data within a Fresnel-zone formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Day-Lewis et al (2002) and Johnson et al (2007) proposed a difference tomography scheme specifically devised to invert time-lapse crosswell amplitude data to map changes in electric conductivity consecutive to a saline tracer test. Very recently, Karaoulis et al (2015) used an active time-constraint approach to invert time-lapse traveltime data within a Fresnel-zone formalism.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that a simultaneous inversion of time-lapse ERT data gives a superior result compared to independent inversions, cascading inversions or differenced inversions. Their preferred technique was a special case of the 4D algorithm of Kim et al (2009), which has also successfully been applied to gravity (Karaoulis et al 2013a), induced polarisation (Karaoulis et al 2013b), and seismic tomography (Karaoulis et al 2015). This technique has not yet been presented for magnetotelluric inversion.…”
Section: Introductionmentioning
confidence: 99%